The Environment And International Politics : International Fisheries, Heidegger and Social Method. - Seckinelgin, Hakan (Taylor & Francis Ltd., 2005)
This book argues that environmental problems represent a deeper problem in the way the relationship between human beings and nature is conceptualised.